2012
DOI: 10.1248/cpb.60.521
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrimidinone Derivatives: Synthesis, Antitumor and Antimicrobial Evaluation

Abstract: Starting from 6-aryl-4-oxo-2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carbonitrile (4a-d), a series of mono-and dialkyl derivatives 5a-j and 6a, b was synthesized. Hydrazinolysis of 4a, b, d and 5d afforded the hydrazino derivatives 7a-c which were cyclised to give the triazolopyrimidinones 8a-c and the pyrimidotriazinones 9a-c through the reaction with formic acid and chloroacetyl chloride, respectively. Most of the newly synthesized compounds were evaluated for their in-vitro antitumor activity. Compounds 6a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…7,14) 2-Alkylthio-6-aryl-4-chloropyrimidine-5-carbonitrile (3a-d) A suspension of 2a-d (0.0017 mol) and phosphorus oxychloride (6 mL) was heated under reflux for 5 h. Excess phosphorus oxychloride was evaporated under reduced pressure to half its volume. The reaction mixture was poured onto ice cold water (15 mL) with continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,14) 2-Alkylthio-6-aryl-4-chloropyrimidine-5-carbonitrile (3a-d) A suspension of 2a-d (0.0017 mol) and phosphorus oxychloride (6 mL) was heated under reflux for 5 h. Excess phosphorus oxychloride was evaporated under reduced pressure to half its volume. The reaction mixture was poured onto ice cold water (15 mL) with continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…The development of potent and effective novel antineoplastic drugs is one of the most intensely persuaded goals of contemporary medicinal chemistry. In view of the biological significance of thiouracils and in continuation of our previous efforts in the synthesis of new thiouracils and uracil-related heterocycles, 7) we would like to report herein the synthesis of new thioxo-chloro-pyrimidines (3b-d), substituted-aminopyrimidines (4a-g) and thiazolopyrimidines (5a-c, 6a-h) and their antitumor, antimicrobial testing. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that some series of 5‐cyano‐2‐thiouracil derivatives showed antimicrobial activities against Staphylococcus aureus , Bacillus subtilis , and Escherichia coli besides their remarkable antifungal activity against Candida albicans and Aspergillus niger . Furthermore, thiouracils exhibited potential therapeutics as antiviral, anticancer, and antimicrobial agents . For example, S ‐alkylation and N ‐alkylation products of pyrimidine‐2‐thione have been recently reported as novel antibacterial, cytotoxic agents , and unique HIV reverse transcriptase inhibitors‐.…”
Section: Introductionmentioning
confidence: 99%
“…Thio substituted pyrimidine derivatives occupy a special position among these compounds. They are also identified as potential antimicrobial and antican cer [11][12][13][14][15][16][17][18], as well as anti inflammatory agents [19]. Prompted by these reports and in continuation of our endeavor on potential anticancer agents [20,21], we have now focused our attention on preparing a series of 6 amino 4 phenyl 2 thioxo 1,2,3,4 tetrahydro pyrimidine 5 carbonitriles (I)-(X) and screened them for antiproliferative activity against human breast cancer (MCF 7), human colon carcinoma (HT29), and non malignant mouse fibroblast (L929) cell lines.…”
Section: Introductionmentioning
confidence: 99%